Tingkat Pengetahuan dan Sikap Tenaga Kesehatan terhadap Triase START - Kencali, Febilla; Utariningsih, Wheny; Iskandar Putri, Baluqia (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2025)
The START (Simple Triage and Rapid Treatment) triage method is a patient classification system based on the severity of injury to determine the priority of treatment in the Emergency Department (ED). The understanding and attitudes of healthcare workers in applying this method impact the effectiveness of care. This study aims to provide an overview of the knowledge and attitudes of healthcare workers in the ED of RSU Cut Meutia Aceh Utara regarding the START triage method. This study is a descriptive survey approach using questionnaires covering aspects of knowledge and attitudes. The respondents are healthcare workers in the ED of RSU Cut Meutia Aceh Utara who meet the inclusion criteria. The data were analyzed univariately and presented in the form of frequency distributions. The results show that the majority of healthcare workers have good knowledge (84.3%), while 9.8% have adequate knowledge, and 5.9% have poor knowledge. Regarding attitudes, 90.2% of healthcare workers have a positive attitude towards the application of the START triage method, while 9.8% have a negative attitude. Additionally, healthcare workers aged 26-35 years (early adulthood), female workers, workers with more than five years of work experience, and those with a Bachelor's degree showed better knowledge and positive attitudes towards the application of triage compared to other groups. In conclusion, healthcare workers at the ED of RSU Cut Meutia Aceh Utara have good knowledge and attitudes towards the START triage method, but continuous training is needed to improve understanding for those with less optimal knowledge and attitudes.